TRANSFORMASI DIGITAL DALAM PELAYANAN RUMAH SAKIT : MENAKAR EFEKTIVITAS, TANTANGAN, DAN IMPLIKASI TERHADAP KUALITAS LAYANAN KESEHATAN DI INDONESIA - Palapessy, Victor E. D; Susanti, Rini (Journal of Hospital Administration and Management (JHAM), 2025)
ABSTRACT ​​Digital transformation in hospital services has become one of the key strategies for improving the quality of healthcare services in Indonesia. This study aims to explore the effectiveness of digital technology implementation, identify challenges encountered during the transformation process, and analyze its implications on the quality of medical services. Using a qualitative approach, the study involves in-depth interviews with ten healthcare professionals from various hospitals across Indonesia. Data analysis was conducted using a thematic method to uncover key patterns in the informants' perceptions and experiences. The findings indicate that digitalization can enhance bureaucratic efficiency and the accuracy of medical records, yet it still faces three major challenges: limited training and adaptation among medical staff, dependency on uneven technological infrastructure, and barriers to digital accessibility—particularly for elderly patients or those unfamiliar with technology. These findings support previous literature highlighting the importance of human resource readiness and supporting systems in the success of digital transformation in the healthcare sector. This study contributes to the development of a conceptual framework for inclusive and sustainable implementation of digital technology in hospitals. Practical implications include the need for designing adaptive training policies and investing in equitable digital infrastructure. Further research is recommended to cover broader geographical contexts and incorporate quantitative analysis to strengthen the generalizability of the findings. Keywords : Hospital digitalization, digital transformation, healthcare services, technological challenges, service effectiveness